Healthcare providers' perceptions of a situational awareness display for emergency department resuscitation: a simulation qualitative study. (29th November 2017) - Calder, Lisa A; Bhandari, Abhi; Mastoras, George; Day, Kathleen; Momtahan, Kathryn; Falconer, Matthew; Weitzman, Brian; Sohmer, Benjamin; Cwinn, A Adam; Hamstra, Stanley J; Parush, Avi
Abstract: Importance: Emergency resuscitation of critically ill patients can challenge team communication and situational awareness. Tools facilitating team performance may enhance patient safety. Objectives: To determine resuscitation team members' perceptions of the Situational Awareness Display's utility. Design: We conducted focus groups with healthcare providers during Situational Awareness Display development. After simulations assessing the display, we conducted debriefs with participants. Setting: Dual site tertiary care level 1 trauma centre in Ottawa, Canada. Participants: We recruited by email physicians, nurses and respiratory therapist. Intervention: Situational Awareness Display, a visual cognitive aid that provides key clinical information to enhance resuscitation team communication and situational awareness. Main outcomes and measures: Themes emerging from focus groups and simulation debriefs. Three reviewers independently coded and analysed transcripts using content qualitative analysis. Results: We recruited a total of 33 participants in two focus groups ( n = 20) and six simulation debriefs with three 4–5 member teams ( n = 13). Majority of participants (10/13) strongly endorsed the Situational Awareness Display's utility in simulation (very or extremely useful). Focus groups and debrief themes included improved perception of patient data, comprehension of context and ability to project to future decisions. Participants described potentially positive and negative impacts on patient safety and positive impacts on provider performance and team communication. Participants expressed a need for easy data entry incorporated into clinical workflow and training on how to use the display. Conclusion: Emergency resuscitation team participants felt the Situational Awareness Display has potential to improve provider performance, team communication and situational awareness, ultimately enhancing quality of care.